Higher institution students' level of awareness, knowledge and attitudes towards people with down syndrome / Intan Nazreene Ahmad and Shakirah Mohd Saad - Ahmad, Intan Nazreene; Mohd Saad, Shakirah (Universiti Teknologi MARA, Perlis, 2018)
People with Down Syndrome (PWDS) are disabled people who a part of the biggest minorities of the society. The main problems faced by them are exclusion from community, discrimination and prejudice. To live with dignity is deemed as a basic right for everyone. Awareness, knowledge and attitudes (AKA) among the general population regarding PWDS vary widely between different countries. In the developed world, public attitude towards PWDS has greatly improved over the years resulting in more favourable social environment. Nevertheless, cultural beliefs and lack of information about PWDS still exist in developing countries. A higher level of education correlates positively with AKA concerning. University students represent a better-educated group of society and it is important that they possess the correct AKA towards disable people. The aim of this study was to determine the current level of AKA among students at a private university in Malaysia. Quantitative Exploratory Research Approach with cross-sectional survey design was the methodology used in this study. The study was conducted within the main campus of the Stanford International College, Penang, Malaysia. It detected that nearly 50 percent of the students were still uncertain on their attitude toward people with PWDS. The results should trigger alertness that much need to be done for our young generation to possess high emotional intelligent. However, the evidence is restricted due to research limitations, including poor measurement, self-selection bias and time constraint.